Field notes contributed by John C. Robinson, fall 1982 - Robinson, John C., 1959-et al (1982)
Field notes were contributed by John C. Robinson and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1982. Epson - sheet feed